Experience of psychiatry distance teaching to english speaking international students - Oprya, Ye.; Melnyk, E.; Pustovoyt, M.; Chernova, T.; Goryachev, P. (Journal of Education, Health and Sport, 2021)
The article describes the difficulties of transition to distance learning (DL) at a medical university when students pass clinical disciplines, using the example of the subject of "psychiatry". The negative impact of the pandemic on international cooperation in the field of education and science was also noted, in particular, attracting foreign students to further education. Based on the above, the following tasks were set: to study the features of the transition to distance learning the subject of "psychiatry" at the Odessa National Medical University, to identify the features of distance work with English-speaking foreign students during their learning of this discipline and to present proposals for optimizing this process. During the transition to DL, a significant decrease in the quality of education was noticed during the absence of an existing learning management system, since this transition was a certain stress for all participants in the educational process, both students and teachers. Significant problems have arisen in the DL of clinical disciplines for English-speaking students. The greatest difficulty is the teaching of psychiatry, since it is difficult to explain to students in English not only the description of psychopathological symptoms and syndromes, but also the mental characteristics of people with other nationalities. It is proposed to use movies, with the main heroes suffering from mental disorders, as a thematic guide for mastering practical skills. Although some of the positive aspects of DL have been noted by medical students, they agree to DL only as a forced short-term measure.